Creative Actualization : a Meliorist Theory of Values. - McDonald, H. P. (Value Inquiry Book., 2010)
This book presents a major new value theory, value as creative actualization. The book takes a radically new approach to values. All potential values, whether artistic, scientific, political, or economic must be creatively actualized in the world. The theory argues for an active view in which value involves creation of novelties and thereby changes the world in some respect. Thus value is neither transcendent nor subjective, as a good of some sort has emerged in the world. Moreover, creative actualization means we can actualize standards, ideals, kinds and other norms. Creative actualization t.